2015
DOI: 10.1007/s00253-015-6853-1
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of new probiotic formulations for gastrointestinal delivery: in vitro study to assess viability and biological properties

Abstract: The paper describes the preparation of new probiotic formulations based on chitosan-coated alginate microcapsules containing three different probiotic strains, Lactobacillus plantarum PBS067, Lactobacillus rhamnosus PBS070, and Bifidobacterium animalis subsp. lactis PBS075 taken individually and as a mixture of them. The effects of microencapsulation on the viability of the strains in conditions simulating the gastrointestinal tract and under industrial processes conditions were studied. In addition, an evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 33 publications
0
29
0
3
Order By: Relevance
“…Among the many diverse biomaterials used for phage encapsulation are cellulose, liposomes, alginate, whey proteins, and gelatin, which have been applied using different techniques1213. Alginate is one of the most common biomaterials used in microencapsulation, including that of probiotics1415 and, as recently shown, bacteriophages. The latter was achieved using alginate either alone or in combination with other components, in which wet capsules ranging in size from 310 μm to almost 1 mm were obtained810161718.…”
mentioning
confidence: 99%
“…Among the many diverse biomaterials used for phage encapsulation are cellulose, liposomes, alginate, whey proteins, and gelatin, which have been applied using different techniques1213. Alginate is one of the most common biomaterials used in microencapsulation, including that of probiotics1415 and, as recently shown, bacteriophages. The latter was achieved using alginate either alone or in combination with other components, in which wet capsules ranging in size from 310 μm to almost 1 mm were obtained810161718.…”
mentioning
confidence: 99%
“…The polymer coating is added in the second step adjusting the procedure previously used for chitosan and briefly consisting of the immersion of the fresh alginate beads in a solution of PVP‐co‐DMAEMA followed by centrifugation. The microcapsules where characterized through fluorescent microscopy ( Figure ) and showed a dimension ranging from 100 to 200 µm.…”
Section: Resultsmentioning
confidence: 99%
“…We recently developed a probiotic formulation containing L. plantarum , encapsulated in alginate‐glucose core and chitosan coating microcapsule . The chitosan coat layer was used to protect alginate core in low gastric pH, while alginate‐glucose and calcium were used as matrix that entraps the probiotic because of the mild gelling conditions of this polymer.…”
Section: Introductionmentioning
confidence: 99%
“…As the development of antibiotic resistance strains continues, the use of probiotics as a substitute for antibiotics is becoming more popular in both the medical field and livestock agriculture (Collins and Gibson, 1999; Collado et al, 2012; Muñoz-Atienza et al, 2013; D’Orazio et al, 2015; Téllez et al, 2015; Varankovich et al, 2015). Probiotic use is defined as the actual application of live beneficial microbes to obtain a desired outcome, may it be prevention of a diseased state or improvement in general health outcome observed in the host organism (Collins and Gibson, 1999).…”
Section: Use Of Probioticsmentioning
confidence: 99%
“…In addition, it has also been demonstrated that maintaining what is considered “normal” microbiota for certain host microbial environments may prevent diseased conditions that are not necessarily of infectious etiology and may improve general health outcome (Franz et al, 2011; Nueno-Palop and Narbad, 2011; Wei et al, 2012; Téllez et al, 2015; Varankovich et al, 2015). As a result, probiotic use, defined as the application of actual live beneficial microbes, has been increasingly practiced for both human and veterinary applications (Tompkins et al, 2008; Vankerckhoven et al, 2008; Sanders et al, 2010; Xiao et al, 2010; Nueno-Palop and Narbad, 2011; Songisepp et al, 2012; Devi et al, 2015; D’Orazio et al, 2015; Fuochi et al, 2015; Senan et al, 2015; Varankovich et al, 2015). Among the modes of probiotic use, the consumption of probiotics through the gastrointestinal route may be considered the most common application in both human and veterinary uses.…”
Section: Introductionmentioning
confidence: 99%